Racial differences in fringe benefits and compensation - Wallace Mok; Zahra Siddique (Institute for the Study of Labor (IZA), 2009)
This paper examines differences in two important components of non-wage compensation, employer provided health insurance and pensions, across African Americans and the whites in the United States. Using data from the Current Population Survey (CPS) and the National Longitudinal Survey of Youth (NLSY), we study the recent trends in the recipiency of this non-wage compensation across race groups. Our results show that African American men on average are significantly less likely to receive employer provided health insurance and pension than whites in the last decade. We also find that the inclusion of racial differences in ability as measured by the Armed Forces Qualification Test (AFQT) score reduces the unexplained racial gap in fringe benefit offers, highlighting the importance of human capital variables in fringe benefit recipiency. Finally, we re-examine racial inequality in the labor market by examining within-group inequality in compensation over the last decade and also the role of ability in between-group inequality in compensation.
urn:nbn:de:101:1-200911041061
Keywords: I11; J15; J32; 330; Economics of minorities and races; non-wage labor costs and benefits; Betriebliche Sozialleistungen; Arbeitsmarktdiskriminierung; Ethnische Diskriminierung; Farbige Bevölkerung; Weiße; USA